The Mediation effect of Value-Co-Creation on Customer Engagement and Positive E-WOM (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2020)
The current study investigates the mediation effect of value-co-creation on customer engagement and positive e-WOM in a competitive Saudi Arabian market. An attempt to illustrate the factors influencing the positive e-WOM as a result of changing customer`s interests and lifestyle. The engagement of consumers in the co-creation of value is powerful in understanding consumer behavior. The paper has made an applied attempt in the Saudi Arabian market to study customer engagement, value co-creation, and positive e-WOM, which adds to the knowledge line in the digital marketing discipline.